Studying the Ability of Thymol to Improve Fungicidal Effects of Tebuconazole and Difenoconazole Against Some Plant Pathogenic Fungi in Seed or Foliar Treatments - Shcherbakova, Larisa; Mikityuk, Oleg; Arslanova, Lenara; Stakheev, Alexander; Erokhin, Denis; Zavriev, Sergey; Dzhavakhiya, Vitaly (Frontiers in Microbiology, 2021)
Thymol, a secondary plant metabolite possessing antifungal and chemosensitizing activities, disrupts cell wall or membrane integrity and interferes with ergosterol biosynthesis. Thymol functions also as a redox-active compound inducing generation of reactive oxygen species and lipid peroxidation in fungal cells. Earlier we showed that thymol significantly enhanced the in vitro growth inhibitory effect of difenoconazole against Bipolaris sorokiniana and Parastagonospora nodorum. Recently, we also demonstrated a possibility to use thymol to overcome the resistance of a P. nodorum strain able to grow on difenoconazole-containing media. However, the possibility to use thymol as a сhemosensitizing agent in seed or plant treatments to provide an effective suppression of the above-mentioned plant pathogens by triazole fungicides applied in lowered dosages remained unproven. In this work, we showed that combined treatments of naturally infected barley seeds with thymol and difenoconazole (Dividend® 030 FS) synergistically exacerbated the protective effect against common root rot agent, B. sorokiniana, and other fungi (Fusarium spp. and Alternaria spp. The similar combined treatments of wheat seeds artificially inoculated with F. culmorum resulted in as much strong reduction of the disease incidence on barley seedlings as the individual application of the tenfold higher Dividend® dosage. In foliar treatments of wheat seedlings, thymol combined with Folicur® 250 EC (a.i. tebuconazole) enhanced the sensitivity of P. nodorum, glume/leaf blotch pathogen, to this fungicide and provided a significant mitigation of the disease severity on treated seedlings compared to the control ones without increasing the fungicidal dosage. Folicur® co-applied with thymol was also much more effective against tebuconazole-tolerant P. nodorum strain than this fungicide alone. No additional deoxynivalenol or zearalenone production was found when a toxigenic F. culmorum was cultured in a nutrient medium containing thymol at a concentration used for chemosensitization of root rot agents. Accordingly, F. culmorum exposure to thymol at the sensitizing concentration did not upregulate key genes associated with the biosynthesis of trichothecene or polyketide mycotoxins in this pathogen. Field trials are necessary to understand if the thymol-triazole co-applications result in a sensitization of seed- and foliar-associated plant pathogenic fungi, and how thymol affect production of fusarioutoxins under field conditions.